Inhaled nitric oxide as adjunctive therapy for severe malaria: a randomized controlled trial. (December 2015) - Hawkes, Michael; Conroy, Andrea; Opoka, Robert; Hermann, Laura; Thorpe, Kevin; McDonald, Chloe; Kim, Hani; Higgins, Sarah; Namasopo, Sophie; John, Chandy; Miller, Chris; Liles, W.; et al.
Abstract Background Severe malaria remains a major cause of childhood mortality globally. Decreased endothelial nitric oxide is associated with severe and fatal malaria. The hypothesis was that adjunctive inhaled nitric oxide (iNO) would improve outcomes in African children with severe malaria. Methods A randomized, blinded, placebo-controlled trial of iNO at 80 ppm by non-rebreather maskversus room air placebo as adjunctive treatment to artesunate in children with severe malaria was conducted. The primary outcome was the longitudinal course of angiopoietin-2 (Ang-2), an endothelial biomarker of malaria severity and clinical outcome. Results One hundred and eighty children were enrolled; 88 were assigned to iNO and 92 to placebo (all received IV artesunate). Ang-2 levels measured over the first 72 h of hospitalization were not significantly different between groups. The mortality at 48 h was similar between groups [6/87 (6.9 %) in the iNO group vs 8/92 (8.7 %) in the placebo group; OR 0.78, 95 % CI 0.26–2.3; p = 0.65]. Clinical recovery times and parasite clearance kinetics were similar (p > 0.05). Methaemoglobinaemia >7 % occurred in 25 % of patients receiving iNO and resolved without sequelae. The incidence of neurologic deficits (<14 days), acute kidney injury, hypoglycaemia, anaemia, and haemoglobinuria was similar between groups (p > 0.05). Conclusions iNO at 80 ppm administered by non-rebreather mask was safe but did not affect circulating levels of Ang-2. Alternative methods of enhancing endothelial NO bioavailability may be necessary to achieve a biological effect and improve clinical outcome. Trial Registration: ClinicalTrials.gov NCT01255215